2013
DOI: 10.1016/j.bbapap.2013.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Long indels are disordered: A study of disorder and indels in homologous eukaryotic proteins

Abstract: This is an accepted version of a paper published in Biochimica et Biophysica ActaProteins and Proteomics. This paper has been peer-reviewed but does not include the final publisher proof-corrections or journal pagination.Citation for the published paper: Light, S., Sagit, R., Ekman, D., Elofsson, A. (2013) "Long indels are disordered: A study of disorder and indels in homologous eukaryotic proteins" Biochimica et Biophysica Acta -Proteins and Proteomics, 1834(5): 890-897 Access to the published version ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 45 publications
4
21
0
Order By: Relevance
“…Significant mutation of framework regions and pronounced use of indels suggest that immune responses to these challenging antigens (1, 14 -16, 39, 40) often require significant remodeling of regions peripheral to the combining site center. Previous analysis of non-IgG protein structures found that indel residues are disordered and preferentially occur in regions of increased disorder tolerant to accommodating new sequences (41)(42)(43)(44)(45)(46). This work extends previous reports demonstrating the importance of secondary mechanisms in antibody diversification beyond V(D)J recombination and AID-mediated single nucleotide mutations.…”
Section: Discussionsupporting
confidence: 78%
“…Significant mutation of framework regions and pronounced use of indels suggest that immune responses to these challenging antigens (1, 14 -16, 39, 40) often require significant remodeling of regions peripheral to the combining site center. Previous analysis of non-IgG protein structures found that indel residues are disordered and preferentially occur in regions of increased disorder tolerant to accommodating new sequences (41)(42)(43)(44)(45)(46). This work extends previous reports demonstrating the importance of secondary mechanisms in antibody diversification beyond V(D)J recombination and AID-mediated single nucleotide mutations.…”
Section: Discussionsupporting
confidence: 78%
“…These include repeat expansion, alternative splicing, and alternative transcription start sites, all of which can influence the length of terminal and/or internal disorder of protein products, thereby potentially influencing the half-life. This idea is supported by the observation that protein disorder is common in insertions and deletions (Light et al, 2013). Furthermore, given that in multicellular eukaryotes (1) alternative transcription start sites commonly generate variation in N termini (Carninci et al, 2006) and (2) alternatively spliced exons are enriched in intrinsic disorder (Buljan et al, 2013), it is likely that such events that generate diversity in protein sequences in different cell types within an individual will have an effect on protein half-life.…”
Section: Discussionmentioning
confidence: 84%
“…Disordered regions often evolve faster than structured regions (Dosztányi et al 2010; Szalkowski and Anisimova 2011; Light et al 2013a). The consequential strong divergence at the sequence level could explain why most largely disordered domain repeat families cannot be matched to any domain HMM in Pfam or SUPERFAMILY.…”
Section: Resultsmentioning
confidence: 99%